Depression and Suicidal Ideations among Older Persons Living with HIV/AIDS in Mbarara City, Southwest Uganda - Amanyire, Jordan Mutambi; Aheisibwe, Irene; Kaggwa, Mark Mohan; Rukundo, Godfrey Zari (Open Journal of Psychiatry, 2023)
Background: Due to the increase in longevity and use of antiretroviral treatment, Uganda has had a growing population of older persons living with HIV/AIDS. However, there is a paucity of information on the mental health of the elderly living with HIV/AIDS. In this cross-sectional study, we determined the prevalence of, and associated factors for depression and suicidal ideation among older persons living with HIV/AIDS in Mbarara city, southwest Uganda. Methods: Older persons (150 females, 115 males), with mean age = 64.2 (±5.1) years, accessing health services from three purposively selected HIV/AIDS care centers in Mbarara city, southwest Uganda were recruited. Data on depression and suicidal ideation were collected using a Patient Health Questionnaire (PHQ-9) validated in Uganda, and a structured questionnaire was used to collect data on clinical and socio-demographic characteristics. Data were analysed using logistic regression. Results: Approximately 8.3% and 12.1% had depression and suicidal ideation, respectively. The factors associated with lowering the likelihood of depression were: an increase in the number of family members they stayed with and having no having any problems with their ARVs. On the other hand, earning more than 100,000 Uganda shillings was associated with reducing the risk of suicidal ideations among the participants. Conclusion: Approximately 8 to 12 in 100 older persons living with HIV/AIDS in Uganda have experienced depression or suicidal ideation. Family support and financial control were instrumental factors associated with depression and suicidal ideations, respectively. We recommended strengthening family structures and creating more avenues for financial independence among older persons living with HIV/AIDS to reduce the burden of depression, and suicidal behaviours among this vulnerable population.
Keywords: Depression; Suicidal Ideation; Older Person; Family Members; Financial Control; HIV/AIDs